Unleashing Nature’s Epigenetic Warriors: Bioactive Compounds and the Nrf2/Keap1 System - Thanh Tran Truc (Chemical Engineering Transactions)
Oxidative stress results from an imbalance between reactive oxygen species (ROS) and endogenous antioxidant defenses, contributing to various diseases. The Nrf2/ARE signaling pathway represents a promising therapeutic target against oxidative stress-mediated disorders, including diabetes, fibrosis, neurotoxicity, and cancer. Dietary phytochemicals derived from herbs and spices have gained attention for their potential health benefits, particularly in relation to Nrf2/ARE system and epigenetic regulation. Some important phytochemicals include: curcumine, quercetin, and sulforaphane. Curcumine obtained from turmeric, curcumin exhibits anti-inflammatory and neuroprotective properties. Curcumin demethylates specific CpG loci within the Nrf2 promoter, enhancing Nrf2 expression. Its epigenetic effects have been observed in various tumor types. Quercetin, resveratrol, and epigallocatechin Gallate (EGCG), these polyphenols modulate Nrf2 signaling by inhibiting Keap1 or activating Nrf2 expression. They enhance the expression of downstream antioxidant enzymes (e.g., HO-1, SOD, CAT). Sulforaphane: Abundant in cruciferous vegetables, sulforaphane activates Nrf2 expression. It also regulates Nrf2 signaling via various kinases (e.g., GSK3beta, PI3/AKT, and MAPK). While existing literature supports the protective effects of dietary phytochemicals against oxidative stress-related diseases, further investigations are required. Future studies should explore additional upstream signaling molecules beyond Nrf2 and elucidate the full impact of phytochemicals on epigenetic regulation. Understanding these mechanisms will pave the way for innovative therapeutic strategies aimed at combating oxidative stress and promoting overall health.